PENGARUH PRODUK DOMESTIK REGIONAL BRUTO DAN DANA DESA TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI ACEH - Muhammad Naufal Al Furqan; Ferayanti Ferayanti (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractThis study aims to analyze how the influence of gross regional domestic product and village funds on the human development index in Aceh Province. The method used in conducting this research is the panel data regression analysis method. This study uses panel data from 23 districts / cities in Aceh Province from 2015-2019. Gross regional domestic product and village funds are the independent variable while the dependent variable is the human development index from BPS Aceh and the Ministry of Finance of the Republic of Indonesia. The results showed that the gross regional domestic product variable had a significant positive effect on the human development index and also the village fund variable had a significant positive effect on the human development index. Partially the dominant influence on the human development index is gross regional domestic product.Keyword: Gross Regional Domestic Product, Village Fund, Human Development Index, Panel Data Regression